Synthesis and Characterization of Urea- doped Calcium, Magnesium and Manganese Phosphate Nanoparticles and Their interaction with Phospho- Bacteria for Sustainable Agriculture Application - Babysalini; Marimuthu A; Rayani Nivethitha P; Chandra Lekha N; Karthika P (The Bioscan, 2026)
Sustainable agricultural production worldwide requires the development of innovative fertilization strategies that enhance agricultural production. The effective utilization of microorganisms in nitrogen fixation can provide a bearable alternative to chemical fertilizers. the design of nano fertilizers that can control nutrient release and delivery is a promising solution offered by nanotechnology. This research investigates the synthesis, characterization, and application of urea- doped calcium, magnesium, and manganese phosphate nanoparticles (CMM-PO4 NPs) as nanofertilizers, both independently and in conjunction with Phosphobacteria, for sustainable agriculture.